Effect of lawsonia inermis on tnbs induced ulcerative colitis in rats. - TAZNEEM. B; ABDULLAH KHAN (International Journal of Pharma and Bio Sciences, 2018)
The study was carried to evaluate phytochemical screening and effect of ethanolic Lawsonia inermis (ELI) extract on 2,4,6-trinitrobenzene sulfonic acid (TNBS) induced ulcerative colitis in rats. Wistar rats (Adult) of either sex were used. Colitis was induced by 20 mg TNBS dissolved in 35% ethanol by single intra-colonic application into the descending colon. Six groups of rats were divided. Animals were treated with ethanol (vehicle), TNBS in 35% ethanol, ELI extract 200 and 400 mg/kg body weight Per oral (p.o) and standard sulfasalazine (SSZ) 360 (mg/kg) p.o. for 14 days. After 14 days of treatment animals were sacrificed and following parameters such as morphological score, histopathology and biochemical parameters like myeloperoxidase (MPO), malondialdehyde (MDA), reduced glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) activity and serum nitrate levels were assessed. ELI found protection against TNBS induced colitis. There was a significant protection with ELI 200 and 400 mg/kg compared to control (P <0.001) group. Morphological and histological score were significantly reduced in all the treated groups (P<0.001). All parameters were altered in colitis induced rats with improvement in animals receiving ELI which was compared to that of standard sulfasalazine treated group. Results indicate the efficacy of ELI against TNBS induced ulcerative colitis in rats.